Rupture uterus: a one year review to find out the causative factors - Gupta, Beena; Bhagat, Prabhat Kumar; Karim, Rezaul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Rupture uterus is a life-threatening obstetric emergency associated with high perinatal mortality. This study aims to find out the common factors associated with this catastrophic condition so as to help in decreasing the incidence of this condition in this study set-up. The objective of this study was to determine incidence, socio-demographic factors, etiology, types of presentation, patterns of management and maternal and fetal outcome in cases of rupture uterus presenting in this study hospital in one year. Methods: In this retrospective study 40 cases of ruptured uterus admitted in the hospital between January to December 2016 were analyzed. Detailed history of relevant socio-demographic factors, prior obstetric and surgical history, clinical findings, nature of management done, fetal and maternal outcome were thoroughly analyzed from the record. Results: A total 40 cases of ruptured uterus during this one-year period out of total 1220 deliveries constituted an incidence of 3%. The commonest age group is 25-30 years (47%). Majority of patients of rupture uterus were those with previous scarred uterus trying for vaginal delivery in hands of dais, untrained birth attendants and midwives. Repair was possible in the majority of cases. There were no maternal deaths but fetal mortality was 92.5%. Conclusions: Proper antenatal care, transportation facilities, good counseling of patients with history of previous uterine surgery for institutional delivery can help in reducing the incidence of rupture uterus in developing countries like India. Prompt surgical intervention can help in reducing the maternal morbidity and mortality associated with rupture uterus.